Penerapan Finiste State Automata Pada Desain Vending Machine Tiket Pakan Hewan Kebun Binatang - Alifudin, M. Iqbal; Gata, Windu; Bayhaqy, Achmad; Hermaliani, Eni Heni; Putra, Jordy Lasmana (LPPM UNIKA Santo Thomas, 2022)
A Zoo is a green open space that used to maintain welfare and exhibit animals for the public. Visitors who come to the zoo reach thousands of people a day and some of them are families who want to have recreation. The enthusiasm of visitors can be seen from visitors who want to give food to animals even though it is prohibited because it is dangerous and the animals have a predetermined diet. This study aims to make a vending machine in the form of purchasing tickets for feeding animals at the zoo with the working principle of a vending machine that implements finite state automata. The method used in this study consists of five stages, the first stage is problem identification, the second stage is system design using UML, the third stage is FSA design using state diagrams, the fourth stage is FSA testing using JFLAP, and the last stage is design of vending machine. The conclusion obtained from this study is that the application of the FSA concept to the pet food ticket vending machine can make transactions as many as 6 animal feeding schedules, this can be useful in adding services to the zoo.